MENYIMAK SEBAGAI KETERAMPILAN BERKOMUNIKASI - Akhiril Pane (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2018)
Learn is a process activity to listen attentive viva voce devices, grasp, appreciation, and interpretation to get information, catching content or send away for and understands communication meaning that passed on by speaker via speech. In gets this activity communication is important so smooth don't it that communication gets to be regarded by learns. Communication is interaction two person or more, appropriate walking communication expectation when that information interchange activity underpinned by information content grasp or send away for that get with every consideration been learnt. So the importance for communication in our life, side involvement in communication in this case order receiver or the audience obviously has skills and can learn. Therefore, learn is that of skill in gets communication